Association of Altered Lipid Profile with Glycemic Status and Anthropometric Indices in Pre-Diabetic and Type 2 Diabetic Patients. A Biochemical Cross-Sectional Study - Amir Jalal, M. Shakil Zari Khawri Siddiqui, Aqib Hanif, Laiba Randhawa, Sana Fatima, Syed Naveed Haider, Muhammad Zahid Randhawa, Razia Batool, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Type 2 diabetes mellitus (T2DM) is increasingly a worldwide health problem; it is frequently preceded by a pre-diabetic state with insidious metabolic changes. Among these, dyslipidemia is the most important factor in accelerating cardiovascular risk. Early risk stratification and intervention depend on understanding the association of lipid profile, glycemic control, and anthropometric indices. Objective: The objective of this cross sectional study was to assess the relationship of altered lipid profile, glycemic status and anthropometric indices among pre diabetic and T2DM patients. Methodology: Fifty pre diabetic and fifty type-2 DM patients aged 18 to 50 years attending a tertiary care hospital were enrolled for a total of 100 adult patients. Lipid profile (total cholesterol, triglycerides, LDL-C, HDL-C) and glycemic parameters (fasting plasma glucose, HbA1c) in fasting blood samples were analyzed. Body mass index (BMI) and waist-to-hip ratio (WHR) were recorded as anthropometric measures. Correlations between lipid parameters, glycemic indices, and anthropometric measures were assessed statistically. Results: Total cholesterol, triglycerides, and LDL cholesterol were significantly (p < 0.05) higher and HDL cholesterol significantly (p < 0.05) lower in T2DM patients compared to pre diabetics. Total cholesterol, triglycerides, and LDL-C (r = 0.34–0.52, p < 0.01) were positively correlated with glycemic parameters (fasting glucose, HbA1c), and negatively correlated with HDL-C (r = –0.28, p < 0.05). Both groups were found to have a positive association of BMI and WHR with triglyceride levels and an inverse association with HDL-C. Conclusion: We find that there is a clear association between altered lipid profiles, poor glycemic control, and adverse anthropometric indices in pre-diabetic and T2DM patients. Dyslipidemia in these groups may be identified early and managed to reduce cardiovascular risk and slow diabetes progression. Keywords: pre-diabetes, type 2 diabetes, lipid profile, glycemic control, anthropometric indices, dyslipidemia